Screening high school students in Italy for sudden cardiac death prevention by using a telecardiology device: a retrospective observational study. (4th March 2016) - De Lazzari, Claudio; Genuini, Igino; Gatto, Maria C.; Cinque, Alessandra; Mancone, Massimo; D'Ambrosi, Alessandra; Silvetti, Elisa; Fusto, Antonio; Pisanelli, Domenico M.; Fedele, Francesco
Abstract: Background: In 2010, an Italian project was launched aimed at using a telecardiology device in order to perform early diagnosis of young students at risk of sudden cardiac death. Methods: Our retrospective observational study was conducted on a population of 13, 016 students, aged between 16 and 19 years, in different Italian regions. It consisted of analysis of data recorded during a telecardiology pilot study. The recorded data were electrocardiograms and data concerning lifestyle habits and family history of cardiovascular diseases. In total, 14 alterations in the electrocardiogram signal have been considered in this study. Some of these alterations are as follows: ventricular ectopic beats, atrioventricular block, Brugada-like electrocardiogram pattern, left anterior/posterior fascicular block, left/right ventricular hypertrophy, long/short QT interval, left atrial enlargement, right atrial enlargement, short PQ interval, and ventricular pre-excitation Wolff–Parkinson–White syndrome. On the basis of the collected data, we implemented this retrospective observational study. Results: The analysed data showed that 13.60% of students had a family history for cardiovascular diseases, 22.43% reported smoking habits, 26.23% reported alcohol consumption, and 7.24% reported abuse of drugs. A total of 24% of students had at least one of the 14 electrocardiogram pathological alterations considered in our study and 32% had electrocardiogram values within the normal range. Conclusions: This retrospective observational study analysed data registered during our telecardiology activity. This activity permitted to maximise data collection and minimise the costs for collecting such data. This activity of screening is being continued and in the next few years it will allow us to have a greater mass of data.